Sosial Ekonomi Masyarakat di Pesisir Pantai Boulevard 2 Kelurahan Maasing Kecamatan Tuminting Kota Manado - Amiri, Virna; Tambas, Jane Sulinda; Pakasi, Caroline Betsi Diana (AGRI-SOSIOEKONOMI, 2023)
Coastal area have slum settlements that are synonymous with a lack of facilities, infrastructure and facilities and can be categorized as uninhabitable houses, and are in locations that are not suitable for formal settlements activities. However, during the presurvey of the houses of the residents of Maasing Village, most of them had fairly good socio-economic conditions and very decent houses to live in. This study aims to determine the socio-economic conditions of the community and describe the socio-economic conditions of the people on the coast. The research was conducted at Boulevard 2, Maasing Tuminting Village, Manado City. The data collection method is a survey. Interview data collection techniques using a questionnaire. The results of the study show that coastal communities have inappropriate social conditions where most of them live under one roof with more than two families, some have a 17x9 house area occupied by twenty people with semi-permanent housing conditions, some have a 6x8 house area occupied by nine people but only has one kitchen. Most of the informants have places to live that are not slums, have very densely populated environmental conditions but still have small vacant lands. The people of the Boulevard 2 coast are not active in organizational activities or the community in the village. However, in the economic condition of the coastal community of Boulevrad 2, Maasing Village has a very good economy, where the income is Rp3.000.000 to Rp8.000.000 per month and most of them have main jobs and even have side jobs.